2022
DOI: 10.3389/fphar.2022.939542
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a hypoxia-stemness-based prognostic signature in pancreatic adenocarcinoma

Abstract: Background: Pancreatic adenocarcinoma (PAAD) is one of the most aggressive and fatal gastrointestinal malignancies with high morbidity and mortality worldwide. Accumulating evidence has revealed the clinical significance of the interaction between the hypoxic microenvironment and cancer stemness in pancreatic cancer progression and therapies. This study aims to identify a hypoxia-stemness index-related gene signature for risk stratification and prognosis prediction in PAAD.Methods: The mRNA expression-based st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…To evaluate the prediction accuracy of the prognosis signature, we calculated the C-index for all published hypoxia-related prognostic signatures in PDAC, whereby a C-index greater than 0.7 is considered indicative of an accurate model. Additionally, we compared the predictive performance of our signature with cell death signatures (autophagy, cuproptosis, ferroptosis, and pyroptosis signatures) [ 60 66 ]. The results showed that the C-index of our signature (0.7286131 in training sets, 0.6163404 in validation sets) surpassed that of other models in both the training and validation sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the prediction accuracy of the prognosis signature, we calculated the C-index for all published hypoxia-related prognostic signatures in PDAC, whereby a C-index greater than 0.7 is considered indicative of an accurate model. Additionally, we compared the predictive performance of our signature with cell death signatures (autophagy, cuproptosis, ferroptosis, and pyroptosis signatures) [ 60 66 ]. The results showed that the C-index of our signature (0.7286131 in training sets, 0.6163404 in validation sets) surpassed that of other models in both the training and validation sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These genes included CD200R1, CD200, TNFRSF4, ICOSLG, ADORA2A, CD160, BTNL2, TNSF14, PDCD1, CD48, CD40LG, TNFRSF25, LAG3, TNFRSF8, CD27, LAIR1, CTLA4, and BTLA ( Figure 10 C). In PAAD, an increased expression of CD44, a marker for cancer stem cells, was closely linked to tumor recurrence and a poor prognosis [ 39 ]. The above-mentioned discrepancies in the expression of invading immune cells between the high- and low-risk groups may be explained by the fact that TNFSF9 was strongly expressed in pancreatic cancer tissues and linked with the M1 polarization of macrophages [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…FBXL17, FBXL8, CDK1, CSNK1D, and PSPC1 have not been well studied in pancreatic ductal cancer. However, several of them have been implicated in pancreatic cancer, with a relatively high expression and a poor survival [30][31][32][33]. These suggest that the 13 genes in this prognostic signature are worth further investigation for their potential as novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%